2014
DOI: 10.3389/fonc.2014.00156
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Dose Escalation in the Treatment of Locally Advanced Non-Small Cell Lung Cancer: Image Guidance and Beyond

Abstract: Radiation dose in the setting of chemo-radiation for locally advanced non-small cell lung cancer (NSCLC) has been historically limited by the risk of normal tissue toxicity and this has been hypothesized to correlate with the poor results in regard to local tumor recurrences. Dose escalation, as a means to improve local control, with concurrent chemotherapy has been shown to be feasible with three-dimensional conformal radiotherapy in early phase studies with good clinical outcome. However, the potential super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…In another study on 137 stage III NSCLC patients and PET-positive areas, local recurrence was reported as 14.6% and distant metastases as 16.8% (67). These findings showed that clinical results of patients with stage II and III disease whose RT were planned by PET were as good as of those planned by using CT (68). Furthermore, the dose to the primary lesion can be increased while preserving the normal tissue in locally advanced NSCLC by using PET.…”
Section: Clinical Results Of Radiotherapy Planning Performed By Positmentioning
confidence: 83%
“…In another study on 137 stage III NSCLC patients and PET-positive areas, local recurrence was reported as 14.6% and distant metastases as 16.8% (67). These findings showed that clinical results of patients with stage II and III disease whose RT were planned by PET were as good as of those planned by using CT (68). Furthermore, the dose to the primary lesion can be increased while preserving the normal tissue in locally advanced NSCLC by using PET.…”
Section: Clinical Results Of Radiotherapy Planning Performed By Positmentioning
confidence: 83%
“…However, no conclusion can be made regarding to the efficacy of IG-IMRT due to this study’s small sample size. Nevertheless, the median survival appears to be better than that observed in most phase III chemo-radiation trials for locally advanced NSCLC, which is usually less than 18 months [ 3 ]. As shown in RTOG 9410, a phase III randomized study assessing the benefit for concurrent vs. sequential chemo-radiation with 3D techniques; the best median survival achieved was 17 months following concurrent chemo-radiation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, advances in technology such as 4DCT and intensity modulated radiotherapy (IMRT) led to lower incidence of radiation-related toxicities and better short-term survival in the treatment of locally advanced non-small cell lung cancer (NSCLC) with chemo-radiation when compared to 3D techniques [ 1 , 2 ]. Treatment accuracy and thoracic OAR sparing can be further improved with daily image guidance due to more accurate tumor localization and the safe PTV margin reduction it allows [ 3 ]. At the current time, image guided (IG)-IMRT may represent one of the best radiotherapy delivery approaches in the treatment of locally advanced lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In another study of 137 patients with stage III NSCLC, local-regional recurrence alone as the first event was only 14.6%, while that combined with distant metastasis as the first event was 16.8% following concurrent chemo-radiation to a median dose of 65 ± 6 Gy when only PET-avid disease was treated ( 40 ). These findings suggest that PET-based planning may lead to at least equivalent clinical outcomes when compared with CT-based planning ( 41 ). However, additional normal tissue sparing may be achieved with PET-based GTV delineation, which may aid dose escalation to the primary tumor to improve the local control of locally advanced NSCLC.…”
Section: Clinical Outcome Following Pet-based Planningmentioning
confidence: 97%